2020
DOI: 10.1016/j.jasrep.2020.102232
|View full text |Cite
|
Sign up to set email alerts
|

Old taphonomy issues, new charcoal data for Mesolithic contexts: Impact of fragment size and sampling context on the assemblages of Escabasses cave (SW France)

Abstract: Does fragment size influence significantly archaeological charcoal spectra? Does the floristic content of charcoal concentrations provide a representative image of the anthracological record? These taphonomy-related questions are as old as the first methodological groundwork in anthracology and therefore, they could be considered as solved. The aim of this paper is to show that they are still topical today, as depositional and post-depositional conditions vary between archaeological contexts, periods, and site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Consequently, specimen sizes vary between members. This is important because a study of the taphonomy in Escabasses Cave (southwestern France) showed that size class does not affect interpretations of floristic diversity (Henry et al, 2020). However, earlier studies by Chabal (1991Chabal ( ,1992Chabal ( , 1997 4.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, specimen sizes vary between members. This is important because a study of the taphonomy in Escabasses Cave (southwestern France) showed that size class does not affect interpretations of floristic diversity (Henry et al, 2020). However, earlier studies by Chabal (1991Chabal ( ,1992Chabal ( , 1997 4.…”
Section: Methodsmentioning
confidence: 97%
“…Approximately 80 specimens of charcoal (Stewart et al, 2016) were analysed from two layers from each member, except from Members 5 BS and 4 WA where more layers were examined (Table 1). Standard anthracological methods were applied to identify the charcoal (see for example Figueiral and Mosbrugger, 2000;Allott, 2006;Théry-Parisot, 2010;Cartwright, 2013;Backwell et al, 2014;Bamford, 2015a, b;Stewart et al, 2016;King et al, 2018;Bodin et al, 2020;Henry et al, 2020). Border Cave specimens were selected for identification by means of random sampling within each sample using random number tables (Drennan, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…If fragment size class sub-sampling is carried out only on certain size fractions from a given sample (i.e., only from the 2-4 mm fraction) these results are also likely to be biased. Subsequent comparisons of their taxon frequency spectra to those contained in the > 4 mm fraction may also reveal differences in sample composition (and the proportions of individual taxa) (e.g., Henry et al, 2020). This is because in the 2-4 mm fraction the absence of fragments >4 mm means that the most frequent taxa in the assemblage, which are more common in the larger size classes, will be under-represented.…”
Section: Sub-sampling With Respect To Fragment Size Classesmentioning
confidence: 99%
“…Another explanation for their dominance could be a differential preservation leading to an over-fragmentation of charcoals. Several studies have shown that post-depositional processes affect charcoal preservation and can induce a bias in the proportions between taxa (Lancelotti et al 2010;Théry-Parisot et al 2010;Chrzazvez et al 2014;Dussol et al 2017;Henry et al 2020). To assess the likelihood of the hypothesis of a differential preservation, we would need this kind of data for each of our taxa, which would require time-consuming experiments.…”
Section: Palaeological Significance: a Firewood Collected Locallymentioning
confidence: 99%